History, forgetfulness and remembrance in Hegel and Nietzsche - Gama, Luis Eduardo (2007)
Despite the evident distance between Hegel’s and Nietzsche’s philosophical projects, there is a shared terrain from which both authors respond to the excesses of Enlightened modernity, which reacted against history and tradition in the name of a subjective consciousness perceived as the unconditioned nucleus of reality. This paper wants to show how close these alleged antagonists are when it comes to sharing an intuition about the fundamental temporality which underlies existence and human experience. From this common vantage, which is, in both cases, hinged on the notions of remem-brance” and forgetfulness”, we strive to generate a vivid –if strained– exchange between Hegel and Nietzsche as critics of modernity.